Al' prav se reče kristalen ali „kristaliničen“? - Humar, Marjeta (Farmacevtski vestnik, 2024)
In order to develop a certain profession and also enrich the language, it is absolutely necessary to develop one's own professional terminology. In this field, Slovenian pharmacy can boast with achievements that only a few European countries may compare with. Concern for terminology goes back more than half a century with the preparation of the translation of the 3rd Yugoslav Pharmacopoeia and work of high quality, especially in the field of pharmaceutical technology. In the last twenty-five years, the most important publications have been the Slovenian supplement to the European Pharmacopoeia, named Formularium Slovenicum, which is updated every year; and the second edition of the Pharmaceutical dictionary.
Keywords: Farmacija; Formularium Slovenicum; Slovarji; strokovna terminologija; terminološki slovar